2016
DOI: 10.1007/s13197-015-2067-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of food materials for development of nutritious pasta utilizing groundnut meal and beetroot

Abstract: Present study was undertaken to optimize the level of food materials viz. groundnut meal, beetroot juice and refined wheat flour for development of nutritious pasta using response surface methodology. Box-benken design of experiments was used to design different experimental combinations considering 10 to 20 g groundnut meal, 6 to 18 mL beetroot juice and 80 to 90 g refined wheat flour. Quality attributes such as protein content, antioxidant activity, colour, cooking quality (solid loss, rehydration ratio and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…The results are in accordance those of [18]. Mridula et al [19] have also shown that the substitution of wheat flour for peanut seed, which is a legume, improves the protein content of pasta.…”
Section: Effect Of Variables On the Protein Content Of Formulationssupporting
confidence: 87%
“…The results are in accordance those of [18]. Mridula et al [19] have also shown that the substitution of wheat flour for peanut seed, which is a legume, improves the protein content of pasta.…”
Section: Effect Of Variables On the Protein Content Of Formulationssupporting
confidence: 87%
“…This was because of the flower petals' purplish color change when exposed to cabinet oven drying and freeze drying. A similar effect on enhancement in appearance was observed when beetroot juice and groundnut meal were added to pasta (Mridula et al, 2016). Additionally, the results compared with the study made on finger millet pasta by Krishnan and Prabhasankar (2010) were similar.…”
Section: Color Analysissupporting
confidence: 67%
“…Singh et al (2016) reported the higher values of total phenolic content and free radical inhibition in corn extrudates by incorporation of beetroot powder at different extrusion temperatures. Mridula et al (2016) has reported use of beetroot juice as a parameter along with groundnut meal and refined wheat flour for development of nutritious pasta that shows high antioxidant activity. The interest in beetroot powder has increased because of the recognition of their potential health benefits.…”
Section: Introductionmentioning
confidence: 99%